Does Zakat Signal the Firm Value? - Ahmad Abbas (Center of Strategic Studies (PUSKAS) BAZNAS, 2020)
Mining and manufacturing industries are two contributive sectors having high economic value. Optimalization of their zakat potential should be estimated not only addressed to provide the gain for public welfare, but firms should also obtain the economic value on their performance. This research aims to provide an empirical inference on mining and manufacturing zakatnomics. The effect of corporate zakat potential on the firms value is tested in this research. The sample comprises 47 mining companies and 180 manufacturing companies listed in Indonesia Stock Exchange by utilizing financial statements of 2018 period. The starting point finds huge the average corporate zakat potential in mining and manufacturing sector. Related to the effect test, the zakat potential is found positive on the firm value. This research also finds that the zakat impacts positively on the profitability. Therefore, it draws an inference that zakat empirically signals firm value and profitability.